2000
DOI: 10.1002/1521-3773(20001016)39:20<3613::aid-anie3613>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Charge Densities of Semiconducting Cage Structures Containing Alkaline Earth Guest Atoms

Abstract: That guest atoms donate electrons to framework atoms is a generally accepted concept. Nevertheless, evidence for the presence of neutral guest atoms in thermoelectric clathrate structures is presented in the form of experimental X‐ray charge density analysis and X‐ray absorption near‐edge structure (XANES) data. The picture shows the deformation density (DD) determined by the maximum entropy method for Ba8Ga16Ge30; the DD shows that both the Ba guest atoms are disordered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 13 publications
3
58
0
1
Order By: Relevance
“…Bentien et al [34] have reported that the 6c, 16i, and 24k sites in the host structure are not randomly occupied by gallium and germanium but a preference for gallium at the 6c site and depletion of gallium at the 16i site in Ba 8 Ga 16 Ge 30 and Sr 8 Ga 16 Ge 30 . Christensen and Iversen [33] pointed out that the engineering of host structure provides a route to manipulate not only the electrical properties but also the thermal conductivity from a thorough investigation of Ba 8 Al 16 Ge 30 clathrates prepared by different synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…Bentien et al [34] have reported that the 6c, 16i, and 24k sites in the host structure are not randomly occupied by gallium and germanium but a preference for gallium at the 6c site and depletion of gallium at the 16i site in Ba 8 Ga 16 Ge 30 and Sr 8 Ga 16 Ge 30 . Christensen and Iversen [33] pointed out that the engineering of host structure provides a route to manipulate not only the electrical properties but also the thermal conductivity from a thorough investigation of Ba 8 Al 16 Ge 30 clathrates prepared by different synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…Chakoumakos et al concluded based on single-crystal neutrondiffraction data on Eu 8 Ga 16 Ge 30 that the framework in that structure is fully disordered, 14 although accurate maximum entropy method analysis of single-crystal x-ray diffraction of Ba 8 Ga 16 Ge 30 and Sr 8 Ga 16 Ge 30 indicate a Ga preference for a specific site (6c of space group number 223͒. 4 In the present refinements a model containing randomly distributed Ga and Ge atoms at each framework site was employed. In the refined model the Eu atoms are located in the centers of the framework voids at the 4c site in space group Cmcm (y Ϸ0.207).…”
Section: B Crystal Structure Refinementmentioning
confidence: 96%
“…[1][2][3][4][5][6][7][8] The inorganic clathrate structures consist of semiconducting frameworks with oversized voids occupied by guest atoms. They can be classified into different types depending on the framework geometry.…”
Section: Introductionmentioning
confidence: 99%
“…In the first examined model of the completely chargebalanced structure full occupation of 16i position by Ga atoms was assumed. From neutron diffraction and XRD structural investigations it is known that 6c position is the most and 16i site is the least preferred position by the trivalent atoms in the host framework [30,31]. However, it follows from Christensen analysis [13] the site occupancy strongly depends on synthesis method.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Among this group of compounds a number of materials derived from Ba 8 Ga 16 Ge 30 composition with high maximum thermoelectric figure-of-merit ZT max values up to 1.35 [2][3][4] have been discovered. Chemical bonding between the guest and the host atoms for most of the intermetallic anionic clathrates is predominantly ionic with a complete electron transfer between the guest and the framework atom [5][6][7]. Therefore, the majority of intermetallic clathrates fulfill Zintl rule and can be regarded as Zintl compounds.…”
Section: Introductionmentioning
confidence: 99%